Mechanisms of Oocyte Maturation and Related Epigenetic Regulation - He, Meina; Zhang, Tuo; Yang, Yi; Wang, Chao (Frontiers in Cell and Developmental Biology, 2021)
Meiosis is the basis of sexual reproduction. In female mammals, meiosis of oocytes starts before birth and sustains at dictyate stage of meiotic prophase I before gonadotropins induced ovulation happens. Once meiosis gets started, the oocytes undergo leptotene, zygotene and pachytene stages, and then arrests at the dictyate stage. During each estrus cycle in mammals, or menstrual cycle in human, a small portion of oocytes within preovulatory follicles may resume meiosis. It is crucial for female to supply high quality mature oocytes for sustaining fertility, which is generally achieved by fine tuning oocytes meiotic arrest and resumption progression. Anything that disturbs the process may result in failure of oogenesis and seriously affect both the fertility and the health of females. Therefore, uncover the regulatory network of oocyte meiosis progression illuminates not only how the foundations of mammalian reproduction are laid, but how mis-regulation of these steps result in infertility. In order to provide an overview of cellular and molecular mechanism the during oocyte maturation especially epigenetic modification been uncovered recently. The progress of the regulatory network of oocyte meiosis progression including meiosis arrest and meiosis resumption induced by gonadotropins are summarized. Then, advances in the epigenetic aspects, such as histone acetylation, phosphorylation, methylation, glycosylation, ubiquitination and sumoylation related to the quality of oocyte maturation are reviewed as well.